Lower Mekong Fish Passage Conference: Applying innovation to secure fisheries productivity. (15th September 2017) - Baumgartner, Lee J.; Boys, Craig A.; Barlow, Chris; Roy, Mike
Summary: The Lower Mekong Basin (LMB) is one of the most biodiverse regions in the world. It contains almost 1, 100 fish species and supports a regional population of almost 60 million people. Fish provide protein, essential micronutrients and income for many of these people. Further, over 85% of fish are migratory and undertake small‐ and large‐scale movements to access spawning, feeding and nursery habitat. In recent times, irrigation and hydropower development have threatened the long‐term sustainability of fisheries resources in the region, and there is a need to develop robust mitigation measures in order to protect and improve fish passage and fisheries productivity. Recognising this, a conference, with 160 delegates from 14 countries brought together global experts in the fields of riverine development, fish passage and aquatic ecosystem management to demonstrate how applied research has been used over the last decade to enhance policy and decision‐making across the LMB and to discuss future directions.